Organizational readiness for the implementation of a three-month short-course TB preventive therapy regimen (3HP) in four health care facilities in Zimbabwe in 2020 - Chisare, Dorothy Tanaka (My University, 2021)
Background: Tuberculosis preventive therapy (TPT) for latent TB infection has had limited success in Zimbabwe. The country plans to roll-out a newer, three-month short-course TPT regimen (3HP) to address the implementation lag and poor uptake of the 6-9-month regimens. The study measured the level of organizational readiness while identifying barriers and facilitators to implement 3HP in four health facilities in Zimbabwe. Methods: A convergent, parallel mixed-methods approach was used to collect data from four primary healthcare clinics in Bulawayo and Harare Metropolitan provinces, Zimbabwe. Twenty healthcare providers completed a 35-item, self-administered questionnaire designed on a 5-point Likert scale and developed from the Weiner organizational readiness model. Nine of the providers and five TB program managers from the Ministry of Health and implementing partners took part in individual semi-structured key-informant interviews. Median scores with interquartile ranges were calculated wherein a score of 3.3 or greater indicated readiness. Differences between facilities were assessed using a Kruskal-Wallis rank test. Qualitative data on barriers and facilitators were transcribed and analyzed using a framework approach. Results: Readiness to implement 3HP across the four facilities was positive with a score of 3.8(IQR 3.3 - 4.1). The difference between the best 4.0(IQR 3.8 - 4.2) and worst performing facility 3.2(IQR 2.7 - 3.3) was 0.8 and statistically significant (p=0.039). The low facility score was due to poor contextual factors 2.5(IQR 2.0 - 3.3), task demands 2.6(IQR 2.3 - 2.9) and resource availability 2.1(IQR 1.5 - 2.5) scores. Key facilitators included provider and management buy-in; collective capability through task-shifting, community willingness to generate demand, alignment with existing primary health care programmes, perceived need, and benefits of 3HP. Barriers were negative past TPT experiences, suboptimal programmatic monitoring, inconsistent provider remuneration, inadequate staffing, erratic supply chain, and an organizational communication gap creating slow program implementation. Conclusions: The varied scores between facilities suggest distinct underlying conditions for readiness. The innovation can reinvigorate healthcare provider motivation in the short term however the erratic supply of resources, absence of TPT-specific monitoring and evaluation, and daily contextual challenges of staff in facilities, must be addressed. Similar research is necessary for countries yet to implement 3HP to optimize the design or revision of delivery strategies and increase uptake of TPT.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science (Implementation Science) to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2021